Pembuatan Studio Podcast SMK Pangeran Antasari Medan - Rinanda Purba; Triadi Sya’Dian; Nazarruddin Nazarruddin (Institut Teknologi dan Bisnis Semarang, 2024)
This journal reviews the implementation of community service activities aimed at building a Podcast studio at SMK Pangeran Antasari. This research was carried out with the aim of improving students' skills in Audio content production and stimulating the development of creativity through Podcast media. The service method includes training, coaching and maintenance of studio facilities. The training involves various aspects, such as technical Audio production, editing, and Podcast marketing. Coaching focuses on idea development, script writing, and presentation skills. Studio facility maintenance includes Hardware and Software management to ensure smooth production. The research results show an increase in students' technical skills in producing Podcasts, along with an increase in their interest and participation in creative activities. The Podcast studio becomes a platform for students to express their ideas, views and talents. In addition, this activity forms a close collaboration between the school and the surrounding community, creating positive synergy and empowering the local community. In conclusion, this community service activity makes a significant contribution to increasing students' media literacy and strengthening the role of SMK Pangeran Antasari as an agent of change in community empowerment through Podcast media.